Structural investigation of the in vitro transcript of the yeast tRNA(phe) precursor by NMR and nuclease mapping. - Hall, K B (1990)
Both NMR and nuclease mapping have been used to probe the structure of an unmodified yeast tRNA(phe) precursor synthesized in vitro by T7 RNA polymerase. A comparison of the NMR data of the precursor and of the mature tRNA transcript shows that the mature tRNA domain structure is similar in both molecules. In the tRNA precursor, the intron consists of a stem of at least four base-pairs, identified by NMR, and two single-stranded loops, identified by nuclease mapping. This is in agreement with the structure previously proposed for the native tRNA(phe) precursor (1). However, our data also show the intron structure to be less stable than the mature tRNA domain, suggesting that the precursor may best be described as having two domains with a hinge at the junction of the anticodon and intron stems.